Analytical studies of scientific publications of the Pharmaceutical journal for 1959-2022 regarding the development of the composition and technology of medicinal products for the treatment of the wound process - Т. M. Оstashchenko; A. V. Lutska (The State Expert Center of the Ministry of Health of Ukraine, 2022)
An actual direction of scientific research is the problem of diagnosis and treatment of infected wounds. An important place in the general structure of diseases of general surgical profile is occupied by patients with purulent-inflammatory diseases of soft tissues, the frequency of which sometimes reaches indicators of 35-40%. With the development of medical science, ideas about wounds and methods of influencing the purulent-inflammatory process are constantly changing. Based on clinical criteria, three consecutive stages (phases) of the development of the wound process with different pathogenesis can be distinguished: purulent-necrotic (inflammatory) - characterized by the presence of necrotic tissues and purulent content in the wound; stage of granulation (regenerative) - manifested by cleaning the wound from purulent-necrotic sequestration and the formation of granulation tissue in it, which gradually fills the wound cavity; stage of epithelization (healing) - epithelization of the wound surface and formation of a scar. The purpose of the work was the analysis of scientific publications of the Pharmaceutical Journal on the development of the composition and technology of drugs for the treatment of the wound process for 1959-2022. The research materials were scientific publications of the scientific and practical edition of the Pharmaceutical Journal for the past 63 years (1959-2022), which used the methods of systematic and structural-logical analysis. The analysis of the scientific publications of the Pharmaceutical Journal over the past 63 years showed that soft drugs for local use do not lose their relevance for a long time. The appearance of new auxiliary substances, scientific knowledge of the wound process creates the basis for the development of new soft drugs and forms for the treatment of the wound process. The following factors are becoming relevant in drug technology: the basis for soft drugs, the correspondence of the phase of the wound process to soft drugs. The medical and biological requirements for the development of soft drugs are also evolving. The analysis of literature data showed that the use of multicomponent ointments on hydrophilic and emulsion bases, which have dehydrating and wound-healing effects, is technologically justified for the local treatment of the wound process. Soft drugs have a leading role in the local treatment of purulent wounds, as they ensure the achievement of the optimal concentration of active pharmaceutical ingredients in the affected area, ensuring high therapeutic efficiency and prolonged effect. Natural components that are part of wound-healing ointments have a significant breadth of pharmacological action, low toxicity and rarely cause side reactions, unlike synthetic agents.